Female Community Health Workers and Health System Navigation in a Conflict Zone: The Case of Afghanistan - Parray, Ateeb Ahmad; Dash, Sambit; Ullah, Md. Imtiaz Khalil; Inam, Zuhrat Mahfuza; Kaufman, Sophia (Frontiers in Public Health, 2021)
Afghanistan ranked 171st among 188 countries in the Gender Inequality Index of 2011 and has only 16% of its women participating in the labor force. The country has been mired in violence for decades which has resulted in the destruction of the social infrastructure including the health sector. Recently, Afghanistan has deployed community health workers (CHW) who make up majority of the health workforce in the remote areas of this country. This paper aims to bring the plight of the CHWs to the forefront of discussion and shed light on the challenges they face as they attempt to bring basic healthcare to people living in a conflict zone. The paper discusses the motivations of Afghani women to become CHWs, their status in the community and within the health system, the threatening situations under which they operate, and the challenges they face as working women in a deeply patriarchal society within a conflict zone. The paper argues that female CHWs should be provided proper accreditation for their work, should be allowed and encouraged to progress in their careers, and should be instilled at the heart of healthcare program planning because they have the field experience to make the most effective and community oriented programmatic decisions.